(untitled) (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2023)
ABSTRACT The purpose of this research is to investigate the effect of Solvency, Profitability, and Going Concern Audit Opinion on Audit Report Lag in JII Companies for the 2018-2021 Period. This secondary data quantitative research uses a purposive sampling technique for panel data. The sample is used for 21 companies registered with JII from 2018 to 2021. Financial reports and annual reports can be accessed at www.idx.co.id. This method is used to collect data. Data were processed using the analysis program Eviews 10. Descriptive test, stationarity test, regression test, classical assumption test, path analysis test, and Sobel test were used to analyze. The results showed that, after conducting road analysis and the Sobel test, the Solvency, Profitability, and Going Concern Audit Opinion variables had no effect on Audit Report Lag. In contrast, the Solvency and Profitability variables affect the Audit Report lag. Keywords: solvency, profitability,going concern audit opinio, and audit report lag